Mechanisms of spectral and temporal integration in the mustached bat inferior colliculus - Wenstrup, Jeffrey J.; Nataraj, Kiran; Sanchez, Jason T. (Frontiers in Neural Circuits, 2012)
This review describes mechanisms and circuitry underlying combination-sensitive response properties in the auditory brainstem and midbrain. Combination-sensitive neurons, performing a type of auditory spectro-temporal integration, respond to specific, properly timed combinations of spectral elements in vocal signals and other acoustic stimuli. While these neurons are known to occur in the auditory forebrain of many vertebrate species, the work described here establishes their origin in the auditory brainstem and midbrain. Focusing on the mustached bat, we review several major findings: 1) Combination-sensitive responses involve facilitatory interactions, inhibitory interactions, or both when activated by distinct spectral elements in complex sounds. 2) Combination-sensitive responses are created in distinct stages: inhibition arises mainly in lateral lemniscal nuclei of the auditory brainstem, while facilitation arises in the inferior colliculus (IC) of the midbrain. 3) Spectral integration underlying combination-sensitive responses requires a low frequency input tuned well below a neuron’s characteristic frequency (ChF). Low-ChF neurons in the auditory brainstem project to high-ChF regions in brainstem or IC to create combination sensitivity. 4) At their sites of origin, both facilitatory and inhibitory combination-sensitive interactions depend on glycinergic inputs and are eliminated by glycine receptor blockade. Surprisingly, facilitatory interactions in IC depend almost exclusively on glycinergic inputs and are largely independent of glutamatergic and GABAergic inputs. 5) The medial nucleus of the trapezoid body, the lateral lemniscal nuclei, and the IC play critical roles in creating combination-sensitive responses. We propose that these mechanisms, based on work in the mustached bat, apply to a broad range of mammals and other vertebrates that depend on temporally sensitive integration of information across the audible spectrum.